A Descriptive Study of Fibromyalgia Syndrome and Low Disease Activity Rheumatoid Arthritis - Khair Muhammad, Ubed Ullah, Seema Shaheen, (Pakistan Journal of Medical & Health Sciences, 2023)
Objectives: To evaluate fibromyalgia syndrome in patients with rheumatoid arthritis (RA) with low disease activity. Settings and sampling: From January 2022 to February 2023, this descriptive research was carried out at Lady Reading Hospital in Peshawar. Based on the ACR 2010 criteria for RA, patients with rheumatoid arthritis were enrolled in the study. Clinical Disease Activity Index (CDAI) scores between 2.5 and 10 were considered mild disease activity, indicating that the disease was of low severity. Based on the 2016 ACR criteria for the diagnosis of fibromyalgia, fibromyalgia syndrome was identified. Results: A total of 78 patients were recruited, and 46 (58.9%) of them were female. Age ranged from 20 to 70 years, with a mean of 41.3±10.6 years. 17 individuals (21.8%) had the fibromyalgia syndrome. Conclusion: Due to the broad discomfort associated with inflammation, substantial disease activity may make a fibromyalgia diagnosis easier. Hence, before diagnosing FMS in a RA patient, strict disease activity management should be taken into account. Keywords: Rheumatoid Arthritis, Low Disease Activity, Fibromyalgia Syndrome,